All Questions Topic List
Differentiation Questions
Previous in All Question Next in All Question
Previous in Differentiation Next in Differentiation
Question Number 62438 by mathsolverby Abdo last updated on 21/Jun/19
splvex2y″−(x+1)y′=(x+1)e−x
Commented by mathmax by abdo last updated on 27/Jul/19
lety′=z(e)⇒x2z′−(x+1)z=(x+1)e−x(he)⇒x2z′−(x+1)z=0⇒x2z′=(x+1)z⇒z′z=x+1x2=1x+1x2⇒ln∣z∣=ln∣x∣−1x+c⇒z=k∣x∣e−1xletdeterminethesolutionon]0,+∞[⇒z(x)=kxe−1xmvcmethod→z′=k′xe−1x+k{e−1x+x1x2e−1x}={k′x+k+kx}e−1x(e)⇒x2{k′x+k+kx}e−1x−(x+1)kxe−1x=(x+1)e−x⇒{k′x3+kx2+kx−kx2−kx}e−1x=(x+1)e−x⇒k′x3=(x+1)e−x+1x⇒k′=x+1x3e1−x2x⇒k(x)=∫.xt+1t3e1−t2tdt+λ⇒z(x)=xe−1x{∫.xt+1t3e1−t2tdt+λ}=λxe−1x+xe−1x∫.xt+1t3e1−t2tdty′(x)=z(x)⇒y(x)=∫z(x)dx+Cy(x)=∫λxe−1xdx+∫(xe−1x∫.xt+1t3e1−t2tdt)dx+C.
Terms of Service
Privacy Policy
Contact: info@tinkutara.com